Meeting the Balance of Electricity Supply and Demand in Latin America and the Caribbean - Yepez-Garcia, Rigoberto Ariel; Johnson, Todd M.; Andres, Luis Alberto (World Bank, 2012)
Economic growth in the Latin America and the Caribbean region has picked up considerably during the past decade or so. This growth has been aided by widespread (earlier and more recent) investments in power generation, transmission, and distribution that increased the provision of electricity services to households, commerce, and industry. This report evaluates a number of critical issues for the power sector in the region in the coming two decades. These include the expected rates of increase in the demand for electricity, the required supply of new generating capacity, the technology and fuel mix of that generating capacity, and the carbon dioxide emissions of the sector. One of the key contributions of this study is the aggregation of individual country plans to the regional and sub regional levels, using a consistent set of data and a common methodology. The report also assesses the important roles of hydropower and natural gas, the way other clean and low-carbon resources can be expanded, the potential and benefits of greater electricity trade, and the role of energy efficiency. By considering the region as a whole, the report highlights the role that individual countries will play in shaping the region's aggregate power sector.